2017
DOI: 10.1080/03949370.2017.1323800
|View full text |Cite
|
Sign up to set email alerts
|

Snake species richness predicts breeding distribution of short-toed snake eagle in central Italy

Abstract: Birds of prey, as top predators, play a key role in ecosystem functioning by regulating prey populations and, by means of cascade effects, promoting biodiversity. This makes them adequate sentinels of ecosystem health. Here we analyse the relationship between the occurrence of breeding short-toed snake eagle (Circaetus gallicus) and both the richness of potential prey species and landscape characteristics by taking into account two different spatial scales (i.e. nest-site scale and landscape scale). The short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Interestingly, neither habitat diversity nor the extent of edge between forests or shrublands and open areas were key factors explaining the presence of the species. Similar results were found in another study carried out in central Italy showing no relationship between the presence of the species and edge extent (Cecere et al 2018). However, other studies have reported that ecotonal and heterogeneous habitats are the preferred hunting areas for the short-toed eagle (Petretti 1988, Sánchez-Zapata & Calvo 1999, Ontiveros 2016).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Interestingly, neither habitat diversity nor the extent of edge between forests or shrublands and open areas were key factors explaining the presence of the species. Similar results were found in another study carried out in central Italy showing no relationship between the presence of the species and edge extent (Cecere et al 2018). However, other studies have reported that ecotonal and heterogeneous habitats are the preferred hunting areas for the short-toed eagle (Petretti 1988, Sánchez-Zapata & Calvo 1999, Ontiveros 2016).…”
Section: Discussionsupporting
confidence: 84%
“…As Cecere et al (2018) hypothesized, we argued that the importance of landscape heterogeneity for the species might arise at higher spatial scales than we analysed, therefore we did not find any significant effect.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation